Cyclotron production of 43Sc and 44gSc from enriched 42CaO, 43CaO, and 44CaO targets - Becker, Kaelyn V.; Aluicio-Sarduy, Eduardo; Bradshaw, Tyler; Hurley, Samuel A.; Olson, Aeli P.; Barrett, Kendall E.; Batterton, Jeanine; Ellison, Paul A.; Barnhart, Todd E.; Pirasteh, Ali; Engle, Jonathan W. (Frontiers in Chemistry, 2023)
Introduction:43Sc and 44gSc are both positron-emitting radioisotopes of scandium with suitable half-lives and favorable positron energies for clinical positron emission tomography (PET) imaging. Irradiation of isotopically enriched calcium targets has higher cross sections compared to titanium targets and higher radionuclidic purity and cross sections than natural calcium targets for reaction routes possible on small cyclotrons capable of accelerating protons and deuterons. Methods: In this work, we investigate the following production routes via proton and deuteron bombardment on CaCO3 and CaO target materials: 42Ca(d,n)43Sc, 43Ca(p,n)43Sc, 43Ca(d,n)44gSc, 44Ca(p,n)44gSc, and 44Ca(p,2n)43Sc. Radiochemical isolation of the produced radioscandium was performed with extraction chromatography using branched DGA resin and apparent molar activity was measured with the chelator DOTA. The imaging performance of 43Sc and 44gSc was compared with 18F, 68Ga, and 64Cu on two clinical PET/CT scanners. Discussion: The results of this work demonstrate that proton and deuteron bombardment of isotopically enriched CaO targets produce high yield and high radionuclidic purity 43Sc and 44gSc. Laboratory capabilities, circumstances, and budgets are likely to dictate which reaction route and radioisotope of scandium is chosen.